1916 Vol. XVI, No. 09, September 1916, Bulletin of the First District Normal School, Kirksville, Missouri, History and Government Series No. 6 - First District Normal School (Kirksville, Mo.) (First District Normal School (Kirksville, Mo.), 1916)
This is a digital copy of the sixth bulletin in the History and Government series, which contains a report on Kingsbury, Rhodes and its development and international relations.